Essential leaf oils of juniperus communis as a repellent of attractant of ornithodoros tartakovskyi - Hughes, Chelsea (My University, 2018)
Soft ticks are vectors of multiple infectious agents, and some of these infectious agents can cause disease in humans and livestock. Therefore, there is a need for a repellent that will prevent soft ticks from feeding on these organisms and transmitting these infectious agents. I placed unfed nymphs in the center of a four-way arena to provide choices among carbon dioxide, J. communis essential leaf oil, J. communis essential leaf oil and carbon dioxide, and a control blank vial to examine the potential of Juniperus communis essential leaf oil as a repellent against the soft tick Ornithodoros tartakovskyi. I used a secondary attachment assay to determine if J. communis essential leaf oil prevented O. tartakovskyi from attaching to a membrane and feeding because a substance may prevent tick-host attachment but not be a repellent. Both assays indicated that J. communis essential leaf oil does not repel O. tartakovskyi but suggested attraction. Based on these results, I tested if J. communis essential leaf oil would attract O. tartakovskyi using a two-way olfactometer. After these trials, it appears that J. communis essential leaf oil does not influence the behavior of O. tartakovskyi, despite the findings of previous studies that demonstrate that such oils repel other species of ticks. The data also suggest that O. tartakovskyi may not behave naturally in a two-way olfactometer when given the choice between a blank control and carbon dioxide because the nymphs were not attracted to carbon dioxide, despite the reliance of ticks on this gas for finding hosts. This study has important implications for finding appropriate natural repellents
"A Thesis submitted in partial fulfillment of the requirements for the degree of Master of Science in Biology"
Keywords: Ticks--Control